Development of Pop Up Book Media on The Material of Indonesian Cultural Diversity To Improve The Learning Outcomes of Grade IV Students of MI NW Bagik Umbung In The 2021/2022 School Year - M. Irwan Mansyuriadi (ASIAN: Indonesian Journal of Learning Development and Innovation, 2023)
The problem behind this research occurs in the learning process related to student learning outcomes that are still below the minimum completeness criteria (KKM = 75), where students who reach the KKM as many as 7 people out of 16 students (43%), have difficulty in remembering the material about the diversity of Indonesian culture, such as the diversity of traditional houses, traditional dances, and traditional clothes, do not create interest in learning and attract students in the learning process. This study aims to develop pop-up book learning media, to analyze the feasibility of the developed pop-up book learning media, and to determine the responses of students and educators to the developed pop-up book learning media. The type of research used is R&D with research and development procedural from Borg and Gall which has been modified by Sugiyono with development steps, namely; (1) the potential and problem stages by observing, (2) the data collection stage by conducting research activities, (3) media design, (4) media validation, (5) media revision phase I, (6) trials, and (7) media revision. This pop-up book learning media was validated by a media expert validator, and tested on educators and fourth grade students of MI NW Bagik Payung.The results showed that the level of validity of the product development of pop up book media on the material of Indonesian cultural diversity according to media experts was 94% in the Very Eligible category. The assessment of the response of educators and students at MI NW Bagik Payung is 100% categorized as Very Practical. And IK (indicator of success) 87.5% categorized as Very Effective. Students are also enthusiastic when participating in learning and are very happy when given learning media in the form of pop up book media.The conclusion of this study is that the pop up book media is effective and appropriate for use in the material on Indonesian cultural diversity for class IV SD/MI. Suggestions for further research is that it is better to develop more interesting learning media to help students learn and perfect the product to get to a mass product.